Body mass index in male patients with COPD: correlation with low attenuation areas on CT. Issue 1 (13th October 2008) - Ogawa, E; Nakano, Y; Ohara, T; Muro, S; Hirai, T; Sato, S; Sakai, H; Tsukino, M; Kinose, D; Nishioka, M; Niimi, A; Chin, K; et al.
Abstract : Background: Chronic obstructive pulmonary disease (COPD) is characterised by the presence of airflow limitation caused by loss of lung elasticity and/or airway narrowing. The pathological hallmark of loss of lung elasticity is emphysema, and airway wall remodelling contributes to the airway narrowing. Using CT, these lesions can be assessed by measuring low attenuation areas (LAA) and airway wall thickness/luminal area, respectively. As previously reported, COPD can be divided into airway dominant, emphysema dominant and mixed phenotypes using CT. In this study, it is postulated that a patient's physique may be associated with the relative contribution of these lesions to airflow obstruction. Methods: CT was used to evaluate emphysema and airway dimensions in 201 patients with COPD. Emphysema was evaluated using percentage of LAA voxels (LAA%) and airway lesion was estimated by percentage wall area (WA%). Patients were divided into four phenotypes using LAA% and WA%. Results: Body mass index (BMI) was significantly lower in the higher LAA% phenotype (ie, emphysema dominant and mixed phenotypes). BMI correlated with LAA% (ρ = −0.557, p<0.0001) but not with WA%. BMI was significantly lower in the emphysema dominant phenotype than in the airway dominant phenotype, while there was no difference in forced expiratory volume in 1 s %predicted between the two. Conclusion: A low BMI is associated with the presence of emphysema, but not with airway wall thickening, in male smokers who have COPD. These results support the concept of different COPD phenotypes and suggest that there may be different systemic manifestations of these phenotypes.